Effects of Saccharomyces boulardii on microbiota composition and metabolite levels in the small intestine of constipated mice - Shuai Tang; Jia Li; Yi Li; Haitao Du; Wenya Zhu; Ru Zhang; Jun Wan (BMC Microbiology)
Abstract Saccharomyces boulardii (S. boulardii) is a fungal probiotic used to treat digestive disorders. However, the mechanism(s) by which S. boulardii affects the small intestine remains unclear. Here, we aimed to explore the effects of S. boulardii on the small intestine and the underlying mechanisms in mice with loperamide-induced constipation. While S. boulardii administration did not fully reverse the alterations in loperamide-induced defecation parameters, it altered the small intestinal floral composition toward a community conducive to alleviate constipation. Moreover, S. boulardii up-regulated the expression of tyrosine-protein kinase Kit (c-Kit), aquaporin 3 (AQP3), interleukin (IL)-10, myosin light chain kinase (MLCK), and phosphorylated myosin light chain 20 (P-MLC20), while concurrently down-regulating the expression levels of inducible nitric oxide synthase (iNOS), p65, and IL-17 A. These alterations indicate a discernible effect of small intestinal water reabsorption, inflammatory factor levels, and smooth muscle contraction. Saccharomyces boulardii also positively regulated small intestinal metabolite levels, such as fructose 6-phosphate, dihomo-alpha-linolenic acid, and 3-(4-hydroxyphenyl) lactate, and participated in metabolic pathways such as arginine biosynthesis, linoleic acid metabolism, and protein digestion and absorption. While not fully reversing defecation changes, Saccharomyces boulardii alters intestinal flora, up-regulates key proteins affecting water reabsorption and inflammation, and positively influences metabolic pathways. Our study provides serves as a basis for further studies on the application of S. boulardii in the treatment of intestinal disorders.